A Revision of Clusia L. Section Cochlanthera (Choisy) Engler A Revision of Clusia L. Section Cochlanthera (Choisy) Engler - Maguire Bassett (Caldasia)
At an earlier time I published (Maguire, 1958) a review of the Section Cochlanthera of the genus Clusia L., admitting there five species. Now, after further field work in Colombia, I present an updated revision of the section with the addition of two new species, bringing the total to seven. At an earlier time I published (Maguire, 1958) a review of the Section Cochlanthera of the genus Clusia L., admitting there five species. Now, after further field work in Colombia, I present an updated revision of the section with the addition of two new species, bringing the total to seven.